2018
DOI: 10.3233/wor-182706
|View full text |Cite
|
Sign up to set email alerts
|

Crane cabins’ interior space multivariate anthropometric modeling

Abstract: The results of this study may prove useful to crane cabin designers in eliminating anthropometric inconsistencies and improving the health of operators, but can also aid in improving the safety, performance and financial results of the companies where crane cabins operate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Moreover, the Workaholism scale has a low correlation (0.28) with the total score of the UWES-9. We believe that this result is in line with Loscalzo and Giannini's [8] proposal of considering workaholism and work engagement as two different constructs that, however, could be co-present, and hence that should be crossed to distinguish between Disengaged and Engaged Workaholics.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the Workaholism scale has a low correlation (0.28) with the total score of the UWES-9. We believe that this result is in line with Loscalzo and Giannini's [8] proposal of considering workaholism and work engagement as two different constructs that, however, could be co-present, and hence that should be crossed to distinguish between Disengaged and Engaged Workaholics.…”
Section: Discussionsupporting
confidence: 89%
“…Again, this item allows to have continuity with previous assessment measures based on the addiction model; however, it is an item that encompasses both the addiction and obsession models. Hence, it is useful to have it in the WI-10, which is an instrument that refers to Loscalzo and Giannini [8] workaholism's definition as a construct comprehending both addiction and obsessive features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5. Space required for accommodation of crane operator in the cabin, in x-y plane when using multivariate approach [18] (a) (b) Figure 6. Node numbers (a) and beam type finite elements (b) in cabin structure geometry model [19] Dynamic calculation of crane cabin structure elements included Eigen-frequencies and main oscillation modes and forced damped oscillation within the frequency range, as shown in Fig.…”
Section: Finite Element Methods Calculations In Innovative Crane Cabinmentioning
confidence: 99%
“…Certain authors such as Pheasant and Haslegrave [17] argue that percentiles approach is neither realistic nor proportioned properly for good-fitting designs and propose application of multivariate approaches. Accordingly, in that aim we propose multivariate modeling such as one described in detail in Essdai et al [18] and shown in Figures 4 and 5.…”
Section: Figure 1 Crane Operators Index Of Un-satisfaction With Currmentioning
confidence: 99%